A comparative study between topical aluminium chloride hexahydrate 20% solution (Driclor) with potassium permanganate KMnO4 solution and topical zinc acetate with erythromycin (Zineryt solution) in treatment of axillary bromhidrosis - Hasan, Anwar Isaa; Latif, Tuqa Mohammed; Hasan, Ethar Falah (Journal of Pakistan Association of Dermatologists, 2023)
Objective To evaluate and compare effectiveness of topical combined driclor solution with Potassium permanganate KMnO4 solution (1:10000) and topical zinc acetate with erythromycin (Zineryt solution) in treatment of axillary bromhidrosis. Methods Across-sectional comparative study was carried out from march 2021 to march 2022. Group A: 25 patients treated with Driclor single night application on dry clean axilla with KMnO4 solution (1:10000) single application at day time for 30 min then wash with tape water. Group B: 25 patients treated with topical zineryt solution twice daily applications for 12 weeks. Follow up of both groups for 12 weeks after stopping the treatment. Results There is no significant difference in mean of severity score for axillary bromhidrosis between group A and group B, before, after 6 weeks and after 12weeks.patients in group A show higher good satisfaction (72%) than group B(12%).during follow up period relapse rate was higher (72% (in group B in compare with relapse rate in group A (16%),percent reduction (response rate) for mean of severity score was 78.37±5.88% after 6 weeks and 91.89±35.29% after 12 weeks in group A and 61.76±4.08 % after 6 weeks and79.41±6.12% after 12 weeks in group B. Conclusion Both protocol was effective in treatment of axillary bromhidrosis, but topical driclor with Potassium permanganate KMnO4 solution (1:10000) show higher response rate and lower relapsing rate when compare with topical zineryt solution.